Chemical constituents of Tetradium sambucinum (Bl.) Hartley - Komala, Ismiarni; Rahmani, Mawardi; Ee, Gwendoline Cheng Lian; Mohd Ismail, Hazar Bebe; Sukari, Mohd Aspollah; Rahmat, Asmah (2006)
Detailed extraction and separation of the aerial parts of Tetradium sambucinum (Bl.) Hartley have led to the isolation of decarine, rutaecarpine, aurantiamide acetate and 7-hydroxycoumarin. The structures of the compounds were established by one and two-dimensional 1H- and 13C-NMR as well other spectroscopic methods. The free radical scavenging and cytotoxic activities were assessed by DPPH assay and against two cancer cell lines, respectively.